Sugemalimab plus chemotherapy vs. chemotherapy for treatment of Chinese patients with esophageal squamous cell carcinoma: a cost effectiveness analysis to inform decision making - Chen, Qiuping; Sun, Quan; Li, Baixue (Frontiers in Oncology, 2025)
BackgroundThe GEMSTONE-304 trial established the clinical benefits of sugemalimab plus chemotherapy in advanced esophageal squamous-cell carcinoma (ESCC). This study evaluates the cost-effectiveness of this regimen versus chemotherapy alone as the first-line treatment for advanced ESCC patients from the perspective of China’s health system.MethodsWe established a partitioned survival model based on GEMSTONE-304 trial data, we simulated lifetime outcomes through three health states: progression-free survival, progressive disease, and death. Key parameters included quality-adjusted life years (QALYs) and incremental cost-effectiveness ratio (ICER), analyzed with 5% discounting. Sensitivity analyses encompassed probabilistic, one-way, and scenario evaluations.ResultsThe sugemalimab combination yielded 0.336 incremental QALYs at $ 44,182.03 additional cost (ICER = $ 131,544.70/QALY). PD-L1 subgroup ICERs exhibited dose-dependent efficacy: $ 187,421.63/QALY (Combined Positive Score (CPS) < 1), $ 175,689.56 (1 ≤ CPS < 10), and $ 130,349.21 (CPS ≥ 10). Scenario analysis demonstrated ICER reduction to $ 51,454.12/QALY under consideration of patient assistance program. None of the results demonstrated cost-effectiveness for this therapeutic regimen. Sensitivity analyses identified sugemalimab pricing as the dominant driver of ICER, while simultaneously validating the model’s internal and external validity. Price cap simulations determined that a minimum 91.20% price reduction is required to achieve cost-effectiveness.ConclusionCurrent pricing renders sugemalimab combination therapy economically unfavorable as first-line ESCC treatment in China. Strategic price adjustments could enhance cost-effectiveness potential.